Time-Course Effects of Acute Aflatoxin B1 Exposure on Hepatic Mitochondrial Lipids and Oxidative Stress in Rats - Rotimi, Oluwakemi A.; Rotimi, Solomon O.; Goodrich, Jaclyn M.; Adelani, Isaacson B.; Agbonihale, Emmanuel; Talabi, Gbemisola (Frontiers in Pharmacology, 2019)
Aflatoxins are secondary metabolites of certain Aspergillus species, that contaminate staple foods, particularly in developing countries. Aflatoxin B1 (AFB1) is the most toxic and common of the major types of aflatoxins. AFB1 is hepatotoxic and has been implicated in increasing the risk of hepatocellular carcinoma (HCC). We have previously shown that subacute exposure to AFB1 for 7 days disrupts hepatic lipids; therefore, this study determined the time-course effects of acute aflatoxin exposure on hepatic mitochondrial lipids and oxidative stress. To achieve this, thirty male albino rats were randomly assigned to six groups. The groups received an oral dose of 1 mg/kg body weight AFB1 or vehicle only (controls) for one, four, or seven days, respectively. Twenty-four hours after the last dose, the animals were sacrificed and liver excised. Mitochondria and cytosolic fractions were obtained from the liver after which lipids (cholesterol, triacylglycerols) were determined in the mitochondria while biomarkers of oxidative stress (glutathione, glutathione transferase (GST), glutathione peroxidase (GPx), glutathione reductase, nitric oxide (NO), malonaldehyde (MDA), thioredoxin reductase (TR) and superoxide dismutase (SOD) were determined spectrophotometrically in the mitochondria and cytosolic fractions. The expression of genes (Nrf2, Acc, Nqo1, and HmgCoa) were determined using quantitative RT-PCR. Results showed that AFB1 significantly increased mitochondrial cholesterol at day seven (treatment vs. control, p=0.016). It also increased the concentrations of NO and MDA at day one and day seven while the activity of GPx and concentration of GSH were increased at day seven (p=0.030) and day one (p=0.025) alone, respectively, compared to control. The activities of cytosolic GR (p=0.014), TR (p=0.046) and GST (p=0.044) were increased at day seven. AFB1 significantly increased the expression of Nrf2 (p=0.029) and decreased the expression of Acc (p=0.005) at day one. This study revealed that AFB1 disrupts hepatic mitochondrial lipids and antioxidant capacity. These changes were dependent on the timing of exposure and did not follow a linear time-course trend. These alterations could be part of the hepatic mitochondria response mechanism to acute AFB1 toxicity. Aflatoxin B1; Liver; Mitochondria; Lipid; Cholesterol; Thioredoxin reductase; oxidative stress